The Efficacy of Guided Imagery-Assisted Systematic Desensitization Group Counseling in Reducing Pre-service Teachers' Public Speaking Anxiety - Ely Roy Madoni; Abidatul Mardliyah; Yurike Kinanthy Karamoy (Universitas Negeri Surabaya, 2026)
Pre-service teachers experience public speaking anxiety as a significant psychological and academic barrier when exposed to teaching practicums. The present study aimed to investigate the effectiveness of Systematic Desensitization Group Counseling with Guided Imagery support in reducing pre-service teachers’ public speaking anxiety. The study was a true experimental study with pretest-posttest control group design. Thirty students who had high levels of anxiety were randomly assigned to an experimental group (n=6) and a control group (n=6). Data were collected by using the adapted Indonesian version of the Personal Report of Public Speaking Anxiety (PRPSA) instrument. Data analysis was performed using the Independent Sample T-Test and Effect Size calculation. The results of the analysis revealed a very significant difference between the experimental and control groups in decreasing the anxiety score (p < 0.001). Calculation of effect size using Cohen’s d resulted in a value of 0.991, which is very large. In summary, the modified guided imagery group counseling intervention of systematic desensitization was highly effective and had a massive impact on suppressing students’ physiological and cognitive anxiety responses. The findings of these studies indicate that the Guidance and Counseling units of universities employ this intervention as a standard mental preparation programme for students before they proceed for teaching practicum